Wild Edible Plants as an Alternative Food Source for The Community of Pakis Baru Village, Nawangan, Pacitan - Cahyanti, Fiky Ariska; Eskundari, Ratna Dewi; Purwanto, Agus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Wild edible plants